Popular Islamic Visual Ideology in Muslim Designer Community’s Digital Da’wah Posters on Instagram - Ahmad Faiz Muntazori; Bambang Sunarto; Tommy Christomy (Lembaga Bale Literasi, 2026)
This article examines the construction of popular Islamic visual ideology in the Instagram da’wah posters of Muslim Designer Community (MDC). Rather than treating da’wah posters merely as media for transmitting religious messages, the article positions them as visual-cultural artifacts in which Islamic meanings are produced through the interplay of text, image, typography, color, composition, and other design elements. The study responds to the limited corpus-based scholarship on how digital da’wah posters organize visual-verbal signs and naturalize particular models of Islamic piety. Employing a qualitative interpretive method, this article analyzes 50 MDC posters selected from 304 Instagram posts published from November 2022 to December 2023 through stratified purposeful sampling across ten themes. Roland Barthes’ semiotics, particularly his “Rhetoric of the Image,” provides the main analytical framework for examining linguistic messages, iconic messages, anchorage, relay, denotation, connotation, myth, and naturalization. The analysis shows that MDC posters rely on titles to anchor visual interpretation, main images to concretize religious values, and supporting texts to extend or legitimize the message. Across the corpus, these visual-verbal relations generate dominant myths of Islam as moral discipline, personal spirituality, practical worship, social ethics, communal solidarity, self-improvement, reflective awareness, and eschatological orientation. The article argues that popular Islam in MDC posters is constructed as a concise, aesthetic, communicative, and digitally compatible form of piety. It contributes to the study of digital da’wah, Islamic visual culture, and semiotic approaches to religious communication.